Senam Ayo Bangkit Senam Ayo Bangkit Training Can Increase Physical Fitness Reviewed From Maximum Oxygen Volume (VO2Max) - Astrawan, I Putu; Prisa Jaya, I Putu (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 2 (2021): Volume 7 No 2 December 2021, 2021)
Physical training has an important role in maintaining and increasing the degree of physical fitness seen from the VO 2 Max ability. The aim of the study was to find out that let's rise up can improve physical fitness in terms of VO 2 Max. This type of experimental research was the randomized pretest posttest control group design. The sample of this study was that of 22 students of the Physiotherapy Study Program divided into 2 groups. Group 1 was given a let's get up and group 2 as a control group, with a frequency of training 3 times a week for 6 weeks. VO 2 Max was measured by the Bleeps Test (MFT) instrument. The normality and homogeneity tests of the data show that the data distribution is normal and homogeneous. The mean intra-group difference test VO 2 Max was tested by using t-paired test. Different test results with t-paired before and after training, Group 1 and Group 2 were significantly different (p <0.05). The VO 2 Max test results between the two groups before and after the training were tested by t-independent sample test. The mean VO 2 Max in the two groups before training was p = 0.21 (p> 0.05) and after training p = 0.00 (p <0.05). In Group 1, the mean VO 2 Max (L / m) before training was 26.34 and the mean after training was 35.48 with a difference of 9.14 and an increase in percentage of 34.70%. Whereas in Group 2, the mean VO 2 Max before training was 25.36 and the mean after training was 27.42 with a difference of 2.06 and an increase of 8.12%. This shows that the treatment of group 1 and group 2 both had an effect. However, the increase in group 1 was better than group 2. It can be concluded that the let's get up exercise training can improve physical fitness in terms of VO 2 Max.